Tax Mimicking in Local Business Taxation: Quasi-experimental Evidence from Portugal - Mariana Lopes da Fonseca (Center for Economic Studies and ifo Institute (CESifo), 2017)
I exploit an exogenous reform introducing a local business tax in Portugal to study tax mimicking among jurisdictions. The identification strategy relies on a quasi-experimental difference-in-differences methodology and heterogeneity in treatment intensity. Results show evidence of significant short-run tax mimicking that decreases over time. I study possible generating processes underlying the strategic interaction among municipalities and find significant evidence of electoral concerns. These electoral concerns are not met with electoral consequences at the local elections, which may be behind the diffusion of local business taxation in the long run.
Keywords: D72; H71; H77; 330; tax mimicking; yardstick competition; local reform